Strategi Manajemen Pembelajaran Guru dalam Meningkatkan Kepuasan Belajar Siswa Sekolah Dasar - Tasya’ah Tasya’ah; Almaytasa Munfarikah; Risyda Dzul Fadlilah; Muhammad Saddam Husein; Nur Rohman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to deeply uncover the learning management tactics implemented by teachers in an effort to improve student learning satisfaction at the elementary school level. Learning satisfaction is an important indicator of the success of the educational process because it is closely related to motivation, active involvement, and student academic outcomes. This study was conducted at SDN 3 Kaliombo, Jepara, using a descriptive qualitative approach. Data collection techniques used included observation of learning activities, interviews with teachers, and documentation in the form of learning notes and class activity plans. The results show that teachers use a variety of innovative and adaptive learning strategies, including a scientific approach, collaborative learning, the use of interactive learning media, and conducive and student-friendly classroom management. The role of teachers is not only as a deliverer of material, but also as a facilitator, motivator, and guide who creates a learning atmosphere that is fun, communicative, and meaningful for students. The tactics used by teachers also consider student characteristics, including their learning styles, levels of understanding, and emotional needs. Active student involvement in the learning process is key to improving their learning satisfaction. This study emphasizes the importance of teachers' role in designing and implementing appropriate learning strategies to support the achievement of educational goals. The implications of these findings suggest that ongoing training for teachers is essential to strengthen their professional capacity in implementing more creative, responsive, and student-oriented learning approaches.